KAJIAN POTENSI PEMBANGKIT LISTRIK TENAGA SURYA DI BANDARA SULTAN ISKANDAR MUDA BANDA ACEH - priyahapsara, istyawan; Pasha, Muhammad Anka (Vortex, 2023)
Sources of electrical energy in Indonesia still use a lot of conversion results from fossil energy such as coal, gas and oil. This fossil energy source is getting less and less and the price keeps going up and contributes a lot of carbon gas emissions that are released into the air, renewable energy, such as solar energy, wind, hydropower, and biomass are alternative energy sources that are environmentally friendly. which needs to be further developed in the future.The author's analysis will take into account the effect of implementing solar panels on several obstacles to the failure of the electricity supply from PLN at Sultan Iskandar Muda International Airport. The purpose of implementing solar panels is to overcome the failure of PLN electricity supply, save electricity costs and reduce carbon gas emissions to the environment in a step to support the concept of an airport with green energy or Eco- Airport, in the calculation method using component analysis, the effect of temperature and also from an economic perspective on the initial investment of the project